Efektivitas stretching exercise terhadap optimalisasi kemandirian lansia - Musripah, Musripah; Wahyuni, Ening (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Aging affects the level of dependency due to declines in biological, psychological, social, and economic functions. Factors affecting the quality of life of older adults include decreased functional abilities, particularly decreased independence, such as decreased walking speed and balance, and an increased risk of falls. This leads to dependence and the need for assistance from others to meet daily needs. Physical activity is one action that can be taken to improve physical fitness, muscle strength, and activities of daily living (ADL), thus enabling older adults to be active and independent. Stretching exercises are gentle muscle stretching exercises for relaxation performed using specific techniques to physiologically reduce muscle tension, based on the principles of mechanical and neurophysiological responses. Stretching is also used to maintain and improve flexibility and mobility of muscles and joints, reducing injuries and postural problems. Purpose: To determine the effectiveness of stretching exercises in optimizing independence in older adults. Method: This study used a quasi-experimental study with a single-group pretest-posttest design. The sampling technique used was purposive sampling, with a sample size of 35 older adults. The research instrument used was the Bartel index questionnaire, and data analysis used a paired t-test. Results: Before the stretching exercise intervention, the average score of participants was 86.86. After the intervention, the score increased to 98.16. This study obtained a p-value of 0.000, indicating that stretching exercises significantly increased the level of independence in the elderly. Conclusion: There was a difference in the level of independence in the elderly before and after the stretching exercise (p-value of 0.000). The stretching exercise intervention increased the independence of the elderly, therefore, this intervention is highly recommended for use in increasing the level of independence in the elderly. Suggestion: Nurses are encouraged to implement stretching exercises to increase the independence of the elderly. Future researchers should consider larger sample sizes, more diverse participant characteristics, and the use of other instruments to measure the level of independence in the elderly. Keywords: Elderly; Independence; Stretching Exercise. Pendahuluan: Lanjut usia memengaruhi tingkat ketergantungan karena akan mengalami kemunduran terhadap fungsi biologis, psikologis, sosial, dan ekonomi. Faktor yang memengaruhi kualitas hidup lansia adalah penurunan kemampuan fungsioanal terutama penurunan tingkat kemandirian, seperti penurunan kecepatan berjalan, kemampuan dalam menjaga keseimbangan dan meningkatnya risiko jatuh, sehingga lansia menjadi ketergantungan dan memerlukan bantuan orang lain dalam hal memenuhi kebutuhan sehari-harinya. Aktivitas fisik merupakan salah satu tindakan yang dapat dilakukan untuk meningkatkan kebugaran fisik, kekuatan otot dan activities daily living (ADLs), sehingga lansia menjadi aktif dan tidak bergantung kepada orang lain. Stretching exercise merupakan latihan peregangan otot ringan untuk relaksasi yang dilakukan menggunakan teknik tertentu untuk menurunkan ketegangan otot secara fisiologis dengan prinsip, terdiri atas respon mekanik dan respon neurofisiologis. Stretching juga digunakan untuk menjaga serta meningkatkan fleksibilitas, mobilitas otot dan area persendian, mengurangi cedera dan masalah dalam postur tubuh. Tujuan: Untuk mengetahui pengaruh efektivitas stretching exercise terhadap optimalisasi kemandirian lansia. Metode: Penelitian ini menggunakan quasi eksperimental dengan desain one group pretest posttest. Teknik pengambilan sampel menggunakan purposive sampling dengan sampel 35 lansia. Instrumen penelitian ini menggunakan kuesioner bartel index dan analisis data menggunakan paired t-test. Hasil: Sebelum dilakukan intervensi exercise stretching, nilai rata-rata partisipan adalah sebesar 86.86. Setelah intervensi, meningkat sebesar 98.16. Hasil penelitian didapatkan p value=0.000, artinya adanya pengaruh exercise stretching terhadap peningkatan tingkat kemandirian pada lansia. Simpulan: Terdapat perbedaan tingkat kemandirian lansia sebelum dan setelah stretching exercise (p value=0.000). Intervensi exercise stretching meningkatkan kemandirian lansia, sehingga intervensi ini lebih direkomendasikan untuk digunakan dalam meningkatkan tingkat kemandirian lansia. Saran: Perawat diharapkan dapat menerapkan exercise stretching untuk meningkatkan kemandirian lansia. Bagi peneliti selanjutnya, dapat mempertimbangkan jumlah sampel yang lebih besar, karakteristik partisipan yang lebih variatif dan penggunaan instrumen lain untuk mengukur tingkat kemandirian lansia. Kata Kunci: Exercise Stretching; Kemandirian; Lansia.